Aspirin resistance in patients with chronic renal failure - (:unkn) unknown (SPRINGER HEIDELBERG, 2011)
Background: Chronic renal failure (CRF) is associated with increased risk of cardiovascular morbidity and mortality. Aspirin resistance worsens clinical prognosis. The aim of this study was to explore the prevalence of aspirin resistance in CRF. Methods: Two hundred and forty-five CRF patients (115 patients undergoing chronic hemodialysis and 130 patients with stage 3-4 chronic kidney disease [CKD]) and 130 patients with normal renal functions (control group) were consecutively recruited. All subjects were taking aspirin regularly. Aspirin responsiveness was determined by Ultegra Rapid Platelet Function Assay-ASA (VerifyNow Aspirin). Aspirin resistance was defined as aspirin reaction unit (ARU) >= 550. Results: Aspirin resistance was detected in 53 patients undergoing hemodialysis, 32 patients with stage 3-4 CKD and 22 controls. The frequency of aspirin resistance was significantly higher in the CRF group compared with controls (34.7% vs. 16.9%, p<0.001) and in hemodialysis patients (46.1%) compared with stage 3-4 CKD patients (24.6%, p<0.001) and controls (16.9%, p<0.001). Multivariate analysis revealed female sex (odds ratio [OR] = 2.201; 95% confidence interval [95% CI], 1.173-4.129; p=0.014), hemodialysis (OR=3.636; 95% CI, 1.313-10.066; p=0.013) and HDL cholesterol (OR=0.974; 95% CI, 0.950-0.999; p=0.043) as independent predictors of aspirin resistance in this cohort of patients. Conclusion: Patients with CRF have higher frequency of aspirin resistance. This might further increase the risk of cardiovascular morbidity and mortality in these patients.
Keywords: Aspirin; Aspirin resistance; Chronic kidney disease; Chronic renal failure; Hemodialysis; LOW-DOSE ASPIRIN; CORONARY-ARTERY-DISEASE; PLATELET RESPONSE; OXIDATIVE STRESS; CARDIOVASCULAR-DISEASE; REDUCED SENSITIVITY; DIABETES-MELLITUS; IIIA POLYMORPHISM; RISK-FACTORS; IN-VITRO